History Teaching in the Republic of Korea: Curriculum and Practice. (1st May 2013) - Kang, Sun Joo
In the Republic of Korea, many history education professionals have focused on what is meant by, and how to develop, students' understanding of the discipline of history while the lay public has been focused on what students should know about the past by the end of their school courses. This article discusses issues around history curriculum and teaching and learning practice in the Republic of Korea. It introduces some Korean research trends in history thinking and students' understanding of history. It also presents issues of historio-graphical disputes among Korea, China and Japan and cultural conflicts between Korean neo-conservative and neo-progressive around national history curriculum.